Teori Belajar Behaviorisme: Teori dan Praktiknya dalam Pembelajaran IPS - Misroh Sulaswari; Nahrul Faidin; Muh Sholeh (Lembaga Pendidikan Hikmatun Najah Blora, 2021)
Purpose of this paper is to explain behaviorism learning theory and its application in social studies learning. Using the literature study method through research studies regarding the implications and application of behaviorism learning theory to various learning in schools. Based on the literature review in this paper, it is found that behaviorism learning theory is very suitable to be applied to learning that requires habituation. Behaviorism theory views that the success of a learning is a change in behavior in a positive direction. In addition, behaviorism theory also prioritizes the mechanism for the formation of learning outcomes through stimulus and response procedures. The learning outcomes achieved are the emergence of the desired behavior through practice and repetition so that learning habits are formed. The application of behaviorism learning theory in social studies learning activities depends on several things, such as the learning objectives, the nature of the learning materials, the characteristics of the students, the available media and learning facilities. Through behaviorism theory, social studies learning needs to be linked to situations and conditions that are relevant to the daily lives of students.Tujuan dari tulisan ini adalah untuk menjelaskan teori belajar behaviorisme dan penerapannya dalam pembelajaran IPS. Menggunakan metode studi literature melalui kajian penelitian mengenai implikasi dan aplikasi teori belajar behaviorisme terhadap berbagai pembelajaran di sekolah. Berdasarkan kajian literatur pada tulisan ini menemukan bahwa teori belajar behaviorisme sangat cocok diterapkan kepada pembelajaran yang membutuhkan pembiasaan. Teori behaviorisme memandang bahwa keberhasilan dari suatu pembelajaran adalah adanya perubahan tingkah laku ke arah positif. Selain itu, teori behaviorisme juga mengutamakan mekanisme terbentuknya hasil belajar melalui prosedur stimulus dan respon. Hasil belajar yang dicapai adalah munculnya perilaku yang diinginkan melalui latihan dan pengulangan sehingga terbentuk kebiasaan belajar. Penerapan teori belajar behaviorisme dalam kegiatan pembelajaran IPS tergantung dari beberapa hal seperti, tujuan pembelajaran, sifat materi pembelajaran, karakteristik peserta didik, media dan fasilitas pembelajaran yang tersedia. Melalui teori behaviorisme maka pembelajaran IPS perlu dikaitkan dengan situasi dan kondisi yang relevan dengan kehidupan sehari-hari peserta didik.